Analysis of Risk Management in Poultry Production Enterprises in Akwa Ibom State (Global Journal of Science Frontier Research, 2023)
The study analyses risk management strategies among poultry enterprises in AkwaIbom State, Nigeria. Multistage sampling technique was to select 122 poultry farmers for the study. Data obtained were analyzed using descriptive, inferential statistics and maximum likelihood estimates. Results of the study revealed that majority 54.9% were male with a mean age of 49 years. All farmers had formal education, 23.2% were primarily farmers with 6 years mean farming experience. The farmers had average household size of 4-6 persons and mean off farm income of N70, 050. About 48.4% were members of cooperative societies and 41.8% had a farm size of 100-200 birds per production cycle. Major sources of risk associated with poultry enterprises in the area included financial/credit risk, health risk and market risk. Most adopted risk management strategies were avoidance measures of fencing and netting and use of foot dips at the entrance. The result of the Maximum Likelihood Estimates revealed that age, off farm income, farm size and medication cost were the factors affecting output of poultry farmers.
Keywords: risk management; risk; poultry; poultry production